From the Past to the Present: Wolf Phylogeography and Demographic History Based on the Mitochondrial Control Region - Ersmark, Erik; Klütsch, Cornelya F. C.; Chan, Yvonne L.; Sinding, Mikkel-Holger S.; Fain, Steven R.; Illarionova, Natalia A.; Oskarsson, Mattias; Uhlén, Mathias; Zhang, Ya-ping; Dalén, Love; Savolainen, Peter (Frontiers in Ecology and Evolution, 2016)
The global distribution of the grey wolf (Canis lupus) is a complex assembly consisting of a large number of populations and described subspecies. How these lineages are related to one another is still not fully resolved, largely due to the fact that large geographical regions remain poorly sampled both at the core and periphery of the species’ range. Analyses of ancient wolves have also suffered from uneven sampling, but have shown indications of a major turnover at some point during the Pleistocene-Holocene boundary in northern North America. Here we analyze variation in the mitochondrial control region in 122 contemporary wolves from some of the less studied populations, as well as six samples from the previously unstudied Greenland subspecies (Canis l. orion) and two Late Pleistocene samples from Siberia. Together with the publicly available control region sequences of both modern and ancient wolves, this study examines genetic diversity on a wide geographical and temporal scale that includes both Eurasia and North America. We identify 13 new haplotypes, of which the majority is found in northern and eastern Asia. The results show that the Greenland samples are all represented by one haplotype, previously identified in North American wolves, among which this population seems to trace its maternal lineage. The phylogeny and network analyses show a wide spatial distribution of several lineages, but also some clusters with more distinct geographical affiliation. In North America, we find support for an end-Pleistocene population bottleneck through coalescent simulations under an approximate Bayesian framework in contrast to previous studies that suggested an extinction-replacement event. However, we find no support for a similar bottleneck in Eurasia. Overall, this global analysis helps to clarify our understanding of the complex history for wolves in Eurasia and North America.